Peran Citra Merek Hijau dan Kesadaran Hijau Terhadap Niat Beli Hijau pada Konsumen IKEA di Indonesia - Dzaky Muhammad Dzulhijj; Anas Hidayat (MAMEN: Jurnal Manajemen, 2023)
Today's furniture industry has developed rapidly and has become a secondary need for all levels of society. Nowadays, there has been a lot of work done on developing green products, and the need has occasionally grown. This is influenced by a number of elements, such as green brand awareness and purchasing intentions, that are environmentally friendly. There is, however, still little research that demonstrates the connection between brand image and environmental awareness and intention to buy. This study aims to analyze the role of green brand image and green awareness in influencing green purchase intentions among IKEA consumers in Indonesia. Quantitative research design by utilizing online questionnaires for data collection to confirm variables of green brand image, green awareness, and green purchase intention in IKEA products in Indonesia. The study included 110 respondents throughout Indonesia who were selected using convenience sampling techniques. Data analysis using SEM-PLS with a confidence level of 95% (p<0.05). According to research, green brand perception positively and significantly affects consumers' intentions to buy green products, while brand perception positively and significantly affects consumers' awareness of green issues, which in turn positively and significantly affects consumers' intentions to buy green products. The study's conclusion is that IKEA products and related businesses should be aware of the factors that influence consumers' intents to buy green products, particularly the green brand's perception and consumer awareness. Thus, it is important to instill knowledge and public awareness to choose environmentally friendly products to instill information that IKEA is top of mind in the development of sustainable environmentally friendly products.